Island-raised but foreign-made: lived experiences, transnational relationships, and expressions of womanhood among Cape Verdean migrant women in Greater Lisbon - Lam, K. (Island Studies Journal, 2021)
Cape Verdeans have migrated to many parts of the world. In Portugal, they are prominent demographically and socially. The archipelago of Cape Verde presents a unique combination of colonial past, immigration history and geographical features that complexifies a study of interpersonal and spatial relationships. The present study has two aims. It seeks to illustrate how Cape Verdean migrant women in Greater Lisbon live, define and negotiate their relationships with people and places, given the transnational configuration of contemporary migration. It also attempts to highlight how these women exercise creativity in expressions and assertions of womanhood. Based on fieldwork, I suggest that Cape Verdean migrant women are historically, socially, and culturally situated subjects. Not only do they possess the capacity to forge meaningful relationships, but they also navigate a sea of multiple and overlapping identities and belongings. They reassess and appropriate interpersonal and spatial relationships with reference to distinct ideas and criteria drawn from their migratory experiences. Taken together, their lived experiences reflect on their self-image as women, mothers, migrants and citizens.